Accumulation of Heavy Metal Lead (Pb) and Effect of Stomates Number on Green Champa Leaves (Polyaltia Longifolia) in Industrial Area of Makassar City - Fahruddin Fahruddin (Hasanuddin University, 2020)
Heavy metal pollution in the industrial area causes problems in the surrounding vegetation. The study aims to determine the absorption of heavy metals lead (Pb) which accumulates on green champa leaves (Polyalthia longifolia) in the industrial area of Makassar city, and its effect on the number of leaf stomata. Leaf samples were taken at three stations, the method used was random sampling. Measurement of the concentration of heavy metals lead (Pb) by the atomic absorption spectrophotometery method (AAS), observation of the number of stomata using a microscope. The results showed the concentration of Pb that accumulated in green champa leaves, such as 1.21–2.42 µg/g. Heavy metals affect stomata on green champa leaves but do not show significant damage (> 0.05). This shows that the green champa plant has benefits in reducing heavy metal pollution in the air, without experiencing damage to the leaf stomata.